A note on lake morphometry, macrophyte vegetation and history of four small mountain lakes in the Northern Black Forest (Germany) - Hansjörg Thies (PANGAEA, 2023)
Dystrophic mountain lakes (i.e. Mummelsee, Herrenwieser See, Schurmsee, Huzenbacher See) in the Northern Black Forest of Germany were investigated during the mid-1980 extquotesingles in the framework of a Diploma thesis. The focus was on atmospheric deposition, lake water chemistry, macrophyte vegetation, and lake morphometry. Here, data on lake morphometry, macrophyte vegetation and history of the studied mountain lakes are presented.